Student Well-Being in the Context of Erik Allardt’s Theory of Welfare and Urie Bronfenbrenner’s Ecological Systems Theory of Development - Łukasik, Izabella Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
Well-being can be described as the balance point between an individual’s resources and difficult events in their life (Dodge et al., 2012). A student’s well-being at school determines their educational success and functioning within their peer group in the school environment (Karataias et al., 2001; Huebner & Gilman, 2002; Polard & Lee, 2003; Engels et al., 2004; Konu & Lintonen, 2005; Soutter et al., 2013; Renshaw et al., 2015; Opre et al., 2018). The purpose of this article is to identify indicators of student well-being in four categories: school conditions, interpersonal relationships, means of self-realization, and health referring to the School Well-Being Model by Konu and Rimpelā (Konu et al., 2002) (based on Allardt’s concept) and situating them in Bronfenbrenner’s socio-ecological system. Having analyzed Erik Allardt’s concept we decided to apply the dimensions of wellbeing he proposes to create measurable categories for recognizing levels of well-being. Allardt identifies three dimensions: having, loving, and being. Students’ assessment of the school situation in the context of individual preferences cannot be neglected, since well-being affects taking on challenges related to various educational tasks. Adequate recognition of difficulties makes it possible to intervene in areas that are most important to promoting well-being. The development and functioning of individuals depend on contexts which are described as the five systems in the ecological model: the microsystem, the mesosystem, the exosystem, the macrosystem, and the chronosystem. The proposed well-being indicators can be used as items in questionnaire studies to obtain a multifaceted view of the conditions that influence students’ sense of well-being. Recognizing the problem correctly allows the student to take corrective measures. The presented structure of student well-being indicators can be supplemented and expanded, to adapt to social, political, and health changes.